Profit Sharing in the German Metalworking and Electrical Engineering Industries. (October 2014) - Haipeter, Thomas; Slomka, Christine
Profit sharing is an increasingly important component of pay in Germany and is the main reason for the intensification of wage drift that has been observed in recent years. However, little is known about how widespread it is, how it is collectively regulated, the regulatory practices that accompany it and the effects those practices have on works councils and unions. These questions are analysed with respect to the development of profit sharing in the German metalworking industry, where it is relatively widespread. Our analysis shows that profit sharing is characterized by ambiguities and contradictions. On the one hand, it is contributing to the ongoing process of wage modernization; on the other hand, however, profit sharing is fuelling trends towards the fragmentation and financialization of pay. Moreover, although driving up actual wages, profit sharing is also a manifestation of an increasing redistribution of income between capital and labour, between firms and between different categories of employee.